Legal Protection Of Investors In The Face Of Insider Trading Practices - Prasetyo, Heny; Prasetyo, Dedy Ardian; Darodjat, Tubagus Achmad (Journal Evidence Of Law, 2025)
This research aims to analyse the legal protection of investors in the face of insider trading practices in the Indonesian capital market. Using the normative juridical method and analytical descriptive approach, this research examines the regulations governing the prohibition of insider trading in Law Number 8 of 1995 concerning the Capital Market, as well as the challenges in implementation and law enforcement against the practice. The results show that although the regulation on insider trading has been clearly regulated, its implementation still faces obstacles in terms of proving transactions and effective supervision. The Financial Services Authority (OJK) has sufficient authority to deal with this, but limited resources and technology utilisation in supervision are the main obstacles. This study recommends increasing supervisory capacity, updating evidentiary-related regulations, and utilising advanced technology to accelerate the detection and prevention of insider trading in the Indonesian capital market